Modulation of biochemical indices in common carp (Cyprinus carpio L.) under the influence of toxic cyanobacterial biomass in diet - Kopp, Radovan; Palíková, Miroslava; Navrátil, Stanislav; Mareš, Jan (Fish physiology and biochemistry, 2014)
Cyanobacteria are producers of potent and environmentally abundant microcystins, representing an emerging global health issue. In the present study, we investigated the impact of cyanobacterial biomass on biochemical indices of common carp (Cyprinus carpio L., average weight of 246 ± 73 g) under laboratory conditions. The fish were fed a diet containing cyanobacterial biomass with microcystins in high concentration (0.4 mg/kg of fish weight and day) for 28 days. Statistical evaluation of the influence of the cyanobacterial biomass in food on the biochemical indices of the juvenile carp showed only minor differences. The activity of aspartate aminotransferase value and the urea concentration were significantly reduced compared to control group. The biochemical parameters of fish blood plasma significantly rose during the experiment in the control group as well as in the experimental group. This state was probably influenced by the environmental conditions and the fish diet. A significant rising value was established in calcium creatinine, total protein, phosphorus, lactate, urea and natrium. The present study demonstrates that the oral exposure of toxic cyanobacterial biomass has a minor influence on the biochemical indices of common carp and that the effect of other factors, e.g., nutrition is more visible.
Keywords: Potassium; dieta; Animal Nutritional Physiological Phenomena; sinice; draslík; krmivo pro zvířata; alanintransaminasa; chloridy; sérový albumin; Cyanobacteria; mořské toxiny; kapři; železo; L-laktátdehydrogenasa; Alanine Transaminase; Marine Toxins; Cholesterol; Bacterial Toxins; Serum Albumin; fyziologie výživy zvířat; Carps; Iron; Chlorides; bakteriální toxiny; zvířata; Microcystins; L-Lactate Dehydrogenase; mikrocystiny; Bilirubin; Animal Feed; bilirubin; Diet; cholesterol; Animals